A self-fluxing alloy material and a method for producing the same

CN122875744APending Publication Date: 2026-10-09POURIN WELDING ENG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611045774.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-14
Publication Date
2026-10-09

AI Technical Summary

Technical Problem

[0003]然而,现有镍基自熔合金在降低熔点与保持韧性之间存在明显矛盾

Benefits of technology

(1)本发明以电解镍板为主体,配合镍硼中间合金、金属硅、镍磷中间合金、电解铜板、金属铬粒、钼粉、海绵钛和金属铌粉形成自熔合金体系,使材料在喷焊和重熔过程中具有较好的熔融铺展性与基体润湿性。镍硼中间合金、金属硅和镍磷中间合金有利于降低熔融温度,电解铜板有利于改善熔体流动状态,金属铬粒和钼粉有利于提高涂层耐蚀性和热稳定性,从而降低高温喷焊对基体的不利影响。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122875744A_ABST
    Figure CN122875744A_ABST
Patent Text Reader

Abstract

The application discloses a kind of self-fluxing alloy material and preparation method thereof in the technical field of metal powder material and surface engineering material, the material includes electrolytic nickel plate, nickel-boron intermediate alloy, metal silicon, electrolytic copper plate, metal chromium particle, molybdenum powder, nickel-phosphorus intermediate alloy, titanium sponge, metal niobium powder, nickel-zirconium alloy, nickel-beryllium intermediate alloy, nickel-cerium intermediate alloy, zirconium-cerium-boron-silicon controlled diffusion composite powder and titanium-niobium-phosphorus oxide carbon composite powder.Two kinds of composite powder are prepared and compounded with main alloy powder, and self-fluxing alloy material is obtained by melting, argon atomization, drying, mixing, vacuum degassing and screening.The material has good melting wetting property, uniform structure, can reduce the spraying temperature, inhibit the diffusion of boron element to the grain boundary of matrix, and improve the toughness, bonding stability and crack resistance of the sprayed layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of metal powder materials and surface engineering materials, specifically relating to a self-fluxing alloy material and its preparation method. Background Technology

[0002] Self-fluxing alloys are widely used for surface strengthening and repair of boiler heating surfaces, heat exchange equipment, wear-resistant pipe fittings, stainless steel components, and high-temperature corrosion-resistant wear parts. These materials are typically applied to the substrate surface via flame spraying, post-spraying remelting, induction remelting, or cladding to form a metallurgical bond layer, thereby improving the wear resistance, corrosion resistance, and thermal shock resistance of the components. Nickel-based self-fluxing alloys are widely used in the surface protection of stainless steel and heat-resistant steels due to their good wettability, oxidation resistance, and process adaptability. To enable the alloy to melt and spread at lower temperatures, existing nickel-based self-fluxing alloys often incorporate melting-reducing elements such as boron, silicon, and phosphorus, giving the melt self-deoxidizing, self-slagging, and self-wetting capabilities, thus improving the density and bonding effect of the sprayed layer.

[0003] However, existing nickel-based self-fluxing alloys present a significant contradiction between lowering the melting point and maintaining toughness. To reduce the spray welding temperature, it is typically necessary to increase the amount of boron and silicon added. However, excessive boron and silicon content can easily promote the formation of hard and brittle borides, silicides, and continuous brittle phases, increasing coating hardness while decreasing plasticity and impact toughness. Especially when spray welding onto stainless steel substrates, boron easily diffuses into the matrix grain boundaries, forming embrittled regions near the fusion line, leading to microcracks, spalling, and premature failure. Traditional self-fluxing alloys also suffer from high melt viscosity, insufficient spreading, coarse microstructure, and significant elemental segregation, making it difficult to simultaneously achieve low heat input, strong bonding, and high toughness under complex thermal cycling and impact loading.

[0004] Therefore, there is an urgent need to develop a new self-fluxing alloy material that, while ensuring low-temperature melting and good wettability, further suppresses the unfavorable diffusion of boron to the matrix grain boundaries, improves the stability of the fusion line structure, and enhances the toughness and crack resistance of the sprayed layer. By constructing a nickel-based low-melting-point alloy system using electrolytic nickel, nickel-boron master alloy, metallic silicon, electrolytic copper, metallic chromium, molybdenum powder, nickel-phosphorus master alloy, sponge titanium, metallic niobium powder, and trace amounts of nickel-zirconium, nickel-beryllium, and nickel-cerium master alloys, and introducing zirconium-cerium-boron-silicon controlled diffusion composite micropowder and titanium-niobium-phosphorus oxide-carbon composite micropowder, it is expected to achieve a synergistic effect of molten pool purification, grain refinement, interface buffering, and diffusion control, thereby solving the problems of high spraying temperature, embrittlement of the bonding interface, insufficient microstructure uniformity, and poor impact resistance of existing self-fluxing alloys. Summary of the Invention

[0005] To address the shortcomings of existing technologies, the present invention aims to provide a self-fluxing alloy material and its preparation method.

[0006] A first aspect of the present invention provides a self-fluxing alloy material comprising the following components in parts by weight: 72.81-76.81 parts electrolytic nickel plate, 10.67-12.00 parts nickel-boron master alloy, 3.80-4.20 parts metallic silicon, 1.90-2.10 parts electrolytic copper plate, 1.10-1.30 parts metallic chromium particles, 0.15-0.25 parts molybdenum powder, 5.00-6.43 parts nickel-phosphorus master alloy, 0.15-0.25 parts sponge titanium, 0.25-0.35 parts metallic niobium powder, 0.015-0.040 parts nickel-zirconium alloy, 0.0075-0.020 parts nickel-beryllium master alloy, 0.15-0.25 parts nickel-cerium master alloy, 0.10-0.25 parts zirconium-cerium-boron-silicon controlled diffusion composite micro powder, 0.08-0.20 parts titanium-niobium-phosphorus oxide-carbon composite micro powder.

[0007] According to a preferred embodiment of the present invention, the preparation method of the zirconium-cerium-boron-silicon controlled diffusion composite micropowder includes: A1. By weight, add 18-22 parts of zirconium nitrate pentahydrate, 10-14 parts of cerium nitrate hexahydrate, 18-25 parts of boric acid, 35-45 parts of acidic silica sol, 3-5 parts of citric acid monohydrate, and 1-3 parts of polyvinylpyrrolidone to a mixed solvent of 180-240 parts of deionized water and 60-90 parts of ethanol. Stir, adjust the pH to 4.0-4.5 with ammonia, and continue stirring to obtain a zirconium-cerium-borosilicate composite sol. Concentrate the zirconium-cerium-borosilicate composite sol to obtain a wet gel. Dry the wet gel to obtain a dry gel. Calcine the dry gel to obtain the calcined product. A2. The calcined product is placed in a nitrogen atmosphere for heat treatment, cooled, and the heat-treated product is obtained; the heat-treated product is ball-milled and sieved.

[0008] In this invention, the formation process of zirconium-cerium-boron-silicon controlled diffusion composite micropowder mainly follows the complexation, sol stabilization, gel fixation, and thermal conversion processes in an acidic water-alcohol system. After zirconium nitrate pentahydrate and cerium nitrate hexahydrate enter a mixed solvent of deionized water and ethanol, they undergo hydration dissociation, with zirconium and cerium ions entering the liquid phase as hydrated positive ions. The carboxyl and hydroxyl groups in citric acid monohydrate coordinate with zirconium and cerium ions to form soluble complex intermediates, inhibiting direct hydrolysis and precipitation under acidic conditions and ensuring uniform distribution of the precursors in the system. Boric acid partially ionizes into borate ions in a weak acid form, which undergo hydrogen bonding and partial condensation with silanol groups on the silica sol surface and hydroxyl groups on the zirconium-cerium complex surface, forming a preliminary borosilicate-oxygen mixed network precursor structure. Acidic silica sol particles, carrying a negative charge on their surface and metastable under low pH conditions, are naturally compatible with the acidic liquid environment formed by the dissociation of zirconium nitrate pentahydrate and cerium nitrate hexahydrate, preventing localized flocculation or uncontrolled gelation due to acid-base shocks. Polyvinylpyrrolidone adsorbs onto the surfaces of silica sol particles and zirconium-cerium complex intermediates, further enhancing system stability through steric hindrance. Upon addition of ammonia, the system pH rises to the gel-sensitive region of 4.0-4.5, where zirconium and cerium ions undergo controlled hydrolysis to form zirconium hydroxyl and cerium hydroxyl species. The silanol groups in the acidic silica sol further condense to form a three-dimensional silica-oxygen framework, and boric acid participates in the construction of the borosilicate network, thus simultaneously immobilizing the four components—zirconium, cerium, boron, and silicon—in the wet gel. After drying at 100-120℃ to remove solvent and free water, nitrate ions decompose to release nitrogen oxides during calcination at 460-540℃. Citric acid and polyvinylpyrrolidone undergo oxidative cracking and are discharged in gaseous form, yielding a calcined product composed of zirconium oxide, cerium oxide, boron-oxygen structure, and silicon-oxygen structure. Further heat treatment at 680-720℃ under a nitrogen atmosphere removes residual volatiles, and zirconium oxide and cerium oxide undergo lattice mutual solubility or close composite formation. The boron-oxygen structure and silicon-oxygen structure form a dispersed boron-silicon-oxygen phase. After ball milling and sieving, a zirconium-cerium-boron-silicon controlled diffusion composite micropowder with uniform particle size is obtained, which can provide nucleation sites, deoxidation purification, and diffusion buffering in the alloy molten system.

[0009] According to a preferred embodiment of the present invention, in step A1, the drying temperature is 100-120°C and the drying time is 8-12h; the calcination temperature is 460-540°C and the calcination time is 1-2h.

[0010] According to a preferred embodiment of the present invention, in step A2, the temperature for heat treatment is 680-720°C and the heat treatment time is 40-80 min.

[0011] According to a preferred embodiment of the present invention, the preparation method of the titanium niobium phosphorus oxide carbon composite micro powder includes: B1. By weight, add 20-28 parts of tetrabutyl titanate to 40-70 parts of anhydrous ethanol to obtain a titanium source solution; add 18-24 parts of ammonium niobate oxalate hydrate, 10-16 parts of ammonium dihydrogen phosphate, 8-12 parts of anhydrous glucose, 3-5 parts of citric acid monohydrate and 1-2 parts of polyethylene glycol 400 to 160-220 parts of deionized water, stir and disperse, adjust the pH to 2.5-3.5 with oxalic acid aqueous solution, and add the titanium source solution dropwise to obtain a titanium-niobium-phosphorus-carbon composite slurry; grind and disperse the titanium-niobium-phosphorus-carbon composite slurry, spray dry to obtain spherical precursor powder; B2. Pre-treat the spherical precursor powder in a nitrogen atmosphere to obtain pre-treated powder; then heat-treat the pre-treated powder in a nitrogen atmosphere, cool, ball-mill, and sieve.

[0012] In this invention, the preparation mechanism of titanium-niobium-phosphorus oxide carbon composite micropowder is based on controlled hydrolysis of the titanium source, complexation and dispersion of the niobium source, fixation of phosphate, and thermal conversion of the carbon source. Tetrabutyl titanate is first dissolved in anhydrous ethanol to form a titanium source solution, avoiding its instantaneous hydrolysis and agglomeration due to direct contact with a large amount of water; ammonium niobate oxalate hydrate is stably dispersed in deionized water as a niobium oxalate complex; ammonium dihydrogen phosphate provides phosphate and dihydrogen phosphate after dissociation; anhydrous glucose is uniformly dissolved in molecular form; citric acid monohydrate assists in complexing the active centers of titanium and niobium through carboxyl groups and adjusts the acidity of the aqueous phase; and polyethylene glycol 400 inhibits particle agglomeration through adsorption. After adjusting the pH of the aqueous phase to 2.5-3.5 using an oxalic acid aqueous solution, oxalate ions preferentially occupy the empty coordination sites of titanium, forming a titanium-oxalic acid complex transition state. This allows the subsequently added tetrabutyl titanate to hydrolyze at a controlled rate to generate titanium hydroxyl species, avoiding independent precipitation of free titanium acid. The generated titanium hydroxyl species coexist in the liquid phase with niobium oxalate complexes, phosphate ions, citric acid monohydrate, and anhydrous glucose through electrostatic adsorption, hydrogen bonding, and coordination, forming a homogeneous titanium-niobium-phosphorus-carbon composite slurry. Grinding and dispersion further homogenize the particle size and distribution of the precursors. Spray drying at an inlet air temperature of 150-180℃ and an outlet air temperature of 80-95℃ rapidly solidifies the titanium, niobium, phosphorus, and carbon precursor components into spherical precursor powder. In the pretreatment stage at 300-360℃ under a nitrogen atmosphere, the spherical precursor powder undergoes decomposition of ammonium salts, oxalate, and citrate, releasing ammonia, carbon dioxide, and water. Anhydrous glucose undergoes dehydration and preliminary carbonization, forming a pretreated powder with uniformly distributed titanium, niobium, phosphorus, and carbon components. Subsequently, during heat treatment at 760-840℃ under a nitrogen atmosphere, the titanium and niobium components are transformed into stable titanium oxide and niobium oxide phases. Phosphate groups form a phosphate solid phase by interfacial bonding with the surfaces of titanium oxide and niobium oxide. The pyrolysis products of anhydrous glucose are further transformed into a dispersed amorphous carbon phase. After cooling, ball milling, and sieving, titanium-niobium-phosphorus oxide-carbon composite micropowder is obtained. This powder can provide interfacial reaction sites related to titanium and niobium during subsequent alloy melting or spray welding, and improves the continuity of the fusion zone structure through the synergistic dispersion effect of the oxide phase and the carbon phase.

[0013] According to a preferred embodiment of the present invention, in step B1, the inlet air temperature of the spray drying is 150-180°C, and the outlet air temperature of the spray drying is 80-95°C.

[0014] According to a preferred embodiment of the present invention, in step B2, the pretreatment temperature is 300-360°C and the pretreatment time is 60-90 min; the heat treatment temperature is 760-840°C and the heat treatment time is 60-120 min.

[0015] In a second aspect, the present invention provides a method for preparing the aforementioned self-fluxing alloy material, comprising the following steps: S1. Electrolytic nickel plates, metallic chromium granules, molybdenum powder, and electrolytic copper plates are added to a melting furnace and melted under an argon atmosphere to obtain a basic melt. Nickel-boron master alloy, metallic silicon, nickel-phosphorus master alloy, sponge titanium, metallic niobium powder, nickel-zirconium master alloy, nickel-beryllium master alloy, and nickel-cerium master alloy are added to the basic melt and refined under an argon atmosphere to obtain an alloy melt. The alloy melt is then atomized with argon gas and sieved to obtain a main alloy powder. The main alloy powder is dried to obtain a dried main alloy powder. S2. Add zirconium-cerium-boron-silicon controlled diffusion composite micro powder and titanium-niobium-phosphorus oxide-carbon composite micro powder to the dry main alloy powder, mix them to obtain a mixed powder; degas the mixed powder under vacuum and sieve it.

[0016] In this invention, the formation mechanism of the self-fluxing alloy material is mainly based on nickel-based melt alloying, low-melting-point eutectic formation, refinement and purification, and post-mixing micro-powder synergy. Electrolytic nickel plate, metallic chromium particles, molybdenum powder, and electrolytic copper plate are first melted in an argon atmosphere to form a basic melt with nickel as the matrix: after entering the nickel-based melt, metallic chromium particles provide a corrosion-resistant base through solid solution, molybdenum powder has a large specific surface area due to its fine particle size, and is fully absorbed in liquid nickel through a dissolution-diffusion mechanism and participates in solid solution strengthening, and electrolytic copper plate reduces the melt viscosity and improves the spreading fluidity during subsequent atomization. Subsequently, nickel-boron master alloy, metallic silicon, nickel-phosphorus master alloy, sponge titanium, metallic niobium powder, nickel-zirconium master alloy, nickel-beryllium master alloy, and nickel-cerium master alloy were added to the base melt. The nickel-boron master alloy, metallic silicon, and nickel-phosphorus master alloy introduced boron, silicon, and phosphorus, respectively, which formed a low-melting-point eutectic system with nickel, significantly reducing the overall melting temperature of the alloy and imparting self-fluxing properties. The titanium introduced by the sponge titanium preferentially combined with free boron to form titanium-boron compounds, weakening the tendency of free boron to migrate and accumulate to the matrix grain boundaries. The niobium introduced by the metallic niobium powder formed a fine niobium-based reinforcing phase, which hindered dislocation movement and crack propagation. The zirconium introduced by the nickel-zirconium master alloy and the cerium introduced by the nickel-cerium master alloy jointly played a role in modification refinement and melt purification, forming inclusions by combining with residual oxygen and sulfur in the melt and floating them out. The nickel-beryllium master alloy provided heterogeneous nucleation sites for the melt in a very small range, inhibiting the continuous growth of coarse grain boundaries. After refining the alloy melt at 1480-1540℃ for 8-15 minutes, it is rapidly solidified into a main alloy powder through argon atomization at 3.0-5.0 MPa. Each alloying element is fixed within fine spherical particles, forming a uniform supersaturated solid solution state. The main alloy powder is then dried and mixed with zirconium-cerium-boron-silicon controlled-diffusion composite micropowder and titanium-niobium-phosphorus oxide-carbon composite micropowder. These two composite micropowders do not participate in the high-temperature reaction during the initial melting stage, avoiding dilution or premature failure during melting. Instead, they are released in the subsequent spray welding or remelting pool, participating in interface regulation and nucleation refinement near the fusion line. The mixed powder is then degassed under vacuum at 120-150℃ for 1-2 hours to remove surface adsorbed water and residual volatile components. The resulting particle size distribution after sieving is suitable for spray welding powder spreading and melt flow, ultimately yielding a self-fluxing alloy material with low melting temperature, good wettability, uniform microstructure, and improved crack resistance in the fusion zone.

[0017] According to a preferred embodiment of the present invention, in step S1, the refining temperature is 1480-1540℃, the refining time is 8-15 min, and the argon atomization pressure is 3.0-5.0 MPa.

[0018] According to a preferred embodiment of the present invention, in step S2, the mixing time is 40-60 min, the vacuum degassing temperature is 120-150 °C, and the vacuum degassing time is 1-2 h.

[0019] Compared with the prior art, the present invention has the following beneficial effects: (1) This invention uses electrolytic nickel plate as the main body, combined with nickel-boron master alloy, metallic silicon, nickel-phosphorus master alloy, electrolytic copper plate, metallic chromium particles, molybdenum powder, sponge titanium and metallic niobium powder to form a self-fluxing alloy system, which makes the material have good melt spreadability and substrate wettability during spray welding and remelting. Nickel-boron master alloy, metallic silicon and nickel-phosphorus master alloy are beneficial to reducing the melting temperature, electrolytic copper plate is beneficial to improving the melt flow state, and metallic chromium particles and molybdenum powder are beneficial to improving the corrosion resistance and thermal stability of the coating, thereby reducing the adverse effects of high-temperature spray welding on the substrate.

[0020] (2) The addition of zirconium-cerium-boron-silicon controlled diffusion composite micropowder in this invention can improve the distribution of inclusions and the solidification nucleation state in the molten pool. The zirconium-cerium-boron-silicon controlled diffusion composite micropowder, prepared from zirconium nitrate pentahydrate, cerium nitrate hexahydrate, boric acid, and acidic silica sol, can promote microstructure refinement during spray welding and mitigate the continuous diffusion of boron in the fusion zone. The combined use of nickel-zirconium alloy, nickel-beryllium master alloy, and nickel-cerium master alloy is beneficial for improving the grain boundary state and reducing the embrittlement tendency at the fusion line.

[0021] (3) The addition of titanium niobium phosphorus oxide carbon composite micropowder to this invention can improve the continuity of the microstructure and crack resistance of the fusion zone. The titanium niobium phosphorus oxide carbon composite micropowder, prepared from tetrabutyl titanate, ammonium niobate oxalate hydrate, ammonium dihydrogen phosphate and anhydrous glucose, works together with sponge titanium and metallic niobium powder to reduce the unfavorable migration of free boron to the matrix grain boundaries and improve crack propagation resistance. After argon atomization, mixing, vacuum degassing and sieving, the resulting material has good low-temperature spray welding adaptability, fusion stability, microstructure uniformity and impact toughness. Attached Figure Description

[0022] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. The drawings are only used to illustrate the implementation methods and are not intended to limit the present invention.

[0023] Figure 1 Metallographic image of the self-fluxing alloy material prepared in Example 1. Detailed Implementation

[0024] To facilitate understanding of the present invention, the following embodiments are provided. Those skilled in the art should understand that these embodiments are merely illustrative and should not be construed as limiting the scope of the invention.

[0025] Example 1 This embodiment provides a method for preparing a self-fluxing alloy material, including the following steps: Step S1: Add 74.81g of electrolytic nickel plate, 1.20g of metallic chromium granules, 0.20g of molybdenum powder, and 2.00g of electrolytic copper plate to a melting furnace, purge with argon gas for 30 minutes, and melt under an argon atmosphere to obtain a basic melt. Add 11.335g of nickel-boron master alloy (Ni-B master alloy, where B content is 15.0wt% and the balance is Ni; the same below), 4.00g of metallic silicon, 5.715g of nickel-phosphorus master alloy (Ni-P master alloy, where P content is 14.0wt% and the balance is Ni; the same below), 0.20g of sponge titanium, 0.30g of metallic niobium powder, and 0.0275g of nickel-zirconium alloy (Ni-Zr master alloy, where Zr content is 20.0wt% and the balance is N) to the basic melt. 0.01375g of nickel-beryllium master alloy (Ni-Be master alloy, where Be content is 2.0wt% and the balance is Ni; the same below) and 0.20g of nickel-cerium master alloy (Ni-Ce master alloy, where Ce content is 10.0wt% and the balance is Ni; the same below) were refined under an argon atmosphere at a refining temperature of 1510℃ for 11.5min to obtain an alloy melt. The alloy melt was then atomized with argon gas at a pressure of 4.0MPa, and the atomized powder was collected. The powder was sieved using a combination of 150μm and 45μm sieves to obtain powder with a particle size of 45-150μm, which was then used to obtain the main alloy powder. The main alloy powder was dried at 120℃ for 2h and cooled to 25℃ to obtain dried main alloy powder. Step S2: Add 0.175g of zirconium-cerium-boron-silicon controlled diffusion composite micro powder and 0.14g of titanium-niobium-phosphorus oxide-carbon composite micro powder to the dry main alloy powder, mix in a three-dimensional mixer for 50min to obtain a mixed powder; degas the mixed powder under vacuum at 135℃ and a vacuum degree not exceeding 100Pa for 1.5h, cool to 25℃, and then sieve using a combination of 150μm and 45μm sieves to obtain powder with a particle size of 45-150μm to obtain the self-fluxing alloy material.

[0026] Preparation steps of zirconium-cerium-borosilicate controlled diffusion composite micropowder: Step A1: Add 210g of deionized water and 75g of ethanol to the reaction vessel, and stir for 10min at 25℃ and 300r / min to obtain a mixed solvent. Add 20g of zirconium nitrate pentahydrate, 12g of cerium nitrate hexahydrate, 21.5g of boric acid, 40g of acidic silica sol, 4g of citric acid monohydrate, and 2g of polyvinylpyrrolidone to the mixed solvent sequentially, and stir for 40min at 25℃ and 400r / min to ensure uniform dispersion of the components. Adjust the concentration with ammonia. Adjust the pH to 4.25 and continue stirring at 25℃ and 400r / min for 60min to obtain a zirconium-cerium-borosilicate composite sol. Concentrate the zirconium-cerium-borosilicate composite sol at 70℃ until the material is in a uniform wet gel state with no obvious free-flowing liquid to obtain a wet gel. Spread the wet gel evenly in a ceramic dish with a thickness of 5mm and dry it at 110℃ for 10h to obtain a dry gel. Grind the dry gel and place it in a crucible, then calcine it at 500℃ for 1.5h to obtain the calcined product. Step A2: Place the calcined product in a tube furnace, purge with nitrogen for 30 minutes, and heat to 700℃ for 60 minutes at a nitrogen flow rate of 1L / min. Cool to 25℃ with the furnace to obtain the heat-treated product. Place the heat-treated product in a ball mill jar, add zirconia grinding balls at a mass ratio of 5:1, and ball mill at 300r / min for 45 minutes. Sieve using a 75μm sieve to obtain zirconium-cerium-boron-silicon controlled diffusion composite micro powder.

[0027] Preparation steps of titanium niobium phosphorus oxide carbon composite micro powder: Step B1: Add 24g tetrabutyl titanate to 55g anhydrous ethanol and stir for 20min at 25℃ and 300r / min to obtain a titanium source solution; add 21g ammonium niobate oxalate hydrate, 13g ammonium dihydrogen phosphate, 10g anhydrous glucose, 4g citric acid monohydrate and 1.5g polyethylene glycol 400 to 190g deionized water and stir for 30min at 25℃ and 400r / min. Adjust the pH to 3.0 with oxalic acid aqueous solution, and then add the titanium source solution dropwise at 25℃ and 400r / min for 30min. After the addition is completed, continue stirring for 60min to obtain a titanium-niobium-phosphorus-carbon composite slurry; grind and disperse the titanium-niobium-phosphorus-carbon composite slurry in a sand mill for 45min, controlling the slurry to have no obvious sedimentation and coarse particles, and then spray dry under the conditions of inlet air temperature of 165℃, outlet air temperature of 87.5℃ and feed rate of 15mL / min to obtain spherical precursor powder; Step B2: Place the spherical precursor powder in a tube furnace, purge with nitrogen for 30 min, and pretreat at 330℃ for 75 min at a nitrogen flow rate of 1 L / min to obtain pretreated powder. Continue to heat treat the pretreated powder in a nitrogen atmosphere at 800℃ for 90 min, cool it to 25℃ with the furnace, place it in a ball mill jar, add zirconia grinding balls at a grinding ball to material mass ratio of 5:1, ball mill at 300 r / min for 45 min, and sieve using a 75 μm sieve to obtain titanium niobium phosphorus oxide carbon composite micro powder.

[0028] Figure 1 The images show metallographic micrographs of the bonding area between the self-fluxing alloy material prepared in Example 1 and the substrate after spray welding. The left image corresponds to a scale bar of 20 μm, and the right image corresponds to a scale bar of 100 μm. The three characteristic areas—the coating area, the bonding interface, and the substrate—are clearly visible. Bonding interface characteristics: As can be seen from the images, the self-fluxing alloy coating and the substrate exhibit a continuous, straight, and defect-free metallurgical bonding interface. No macroscopic defects such as porosity, inclusions, cracks, or lack of fusion are observed. The interface transition is natural, exhibiting a clear elemental interdiffusion band, indicating that the zirconium-cerium-boron-silicon controlled diffusion composite micropowder added in this invention effectively regulates the diffusion behavior of elements such as B, P, and Si, avoiding interface dilution and component segregation caused by excessive diffusion, while ensuring good wetting, spreading, and metallurgical bonding strength. Coating area microstructure characteristics: The upper coating area in the right image has a dense and uniform microstructure, exhibiting typical characteristics of a Ni-based self-fluxing alloy γ-Ni solid solution matrix + dispersed reinforcing phase composite microstructure. The matrix is ​​a light-colored γ-Ni solid solution containing fine, uniform hard phase particles dispersed within it, without coarse dendrites or obvious agglomeration. This is attributed to the synergistic refining and purifying effects of trace elements such as Ti, Nb, Zr, Ce, and Be, as well as the heterogeneous nucleation particles introduced by the titanium-niobium-phosphorus oxide-carbon composite micropowder, which together inhibit the growth of the primary phase and significantly refine the microstructure. Matrix-side microstructure: The lower part of the matrix in the right figure exhibits a typical dendritic pattern, forming a sharp contrast with the coating, further confirming the clear and complete coating-matrix interface. In summary, the self-fluxing alloy material cladding layer prepared in Example 1 has a dense microstructure, good interfacial bonding, and fine, dispersed hard phases, verifying the effectiveness of the formulation and process of this invention.

[0029] Example 2 The difference between this embodiment and Embodiment 1 is that this embodiment provides a method for preparing a self-fluxing alloy material, including the following steps: Step S1: Add 72.81g of electrolytic nickel plate, 1.10g of metallic chromium granules, 0.15g of molybdenum powder, and 1.90g of electrolytic copper plate to a melting furnace, purge with argon gas for 30 minutes, and melt under an argon atmosphere to obtain a basic melt; add 10.67g of nickel-boron master alloy, 3.80g of metallic silicon, 5.00g of nickel-phosphorus master alloy, 0.15g of sponge titanium, 0.25g of metallic niobium powder, 0.015g of nickel-zirconium alloy, and 0.0075g of nickel-beryllium to the basic melt. The master alloy and 0.15g of nickel-cerium master alloy were refined under an argon atmosphere at a temperature of 1480℃ for 8 minutes to obtain an alloy melt. The alloy melt was then atomized with argon gas at a pressure of 3.0MPa, and the atomized powder was collected. The powder was then sieved using a combination of 150μm and 45μm sieves to obtain powder with a particle size of 45-150μm, which was then used to obtain the main alloy powder. The main alloy powder was dried at 120℃ for 2 hours and then cooled to 25℃ to obtain dried main alloy powder. Step S2: Add 0.10g of zirconium-cerium-boron-silicon controlled diffusion composite micro powder and 0.08g of titanium-niobium-phosphorus oxide-carbon composite micro powder to the dry main alloy powder, mix in a three-dimensional mixer for 40min to obtain a mixed powder; degas the mixed powder under vacuum at 120℃ and a vacuum degree not exceeding 100Pa for 1h, cool to 25℃ and then sieve using a combination of 150μm and 45μm sieves to obtain powder with a particle size of 45-150μm to obtain the self-fluxing alloy material.

[0030] Preparation steps of zirconium-cerium-borosilicate controlled diffusion composite micropowder: Step A1: Add 180g of deionized water and 60g of ethanol to the reaction vessel, and stir for 10min at 25℃ and 300r / min to obtain a mixed solvent. Add 18g of zirconium nitrate pentahydrate, 10g of cerium nitrate hexahydrate, 18g of boric acid, 35g of acidic silica sol, 3g of citric acid monohydrate, and 1g of polyvinylpyrrolidone to the mixed solvent sequentially, and stir for 40min at 25℃ and 400r / min to ensure uniform dispersion of the components. Then, use ammonia water... The pH was adjusted to 4.0, and the mixture was stirred at 25℃ and 400 r / min for 60 min to obtain a zirconium-cerium-borosilicate composite sol. The zirconium-cerium-borosilicate composite sol was concentrated at 70℃ until the material was in a uniform wet gel state with no obvious free-flowing liquid to obtain a wet gel. The wet gel was spread evenly in a ceramic dish with a thickness of 5 mm and dried at 100℃ for 8 h to obtain a dry gel. The dry gel was crushed and placed in a crucible and calcined at 460℃ for 1 h to obtain the calcined product. Step A2: Place the calcined product in a tube furnace, purge with nitrogen for 30 min, and heat to 680℃ for 40 min at a nitrogen flow rate of 1 L / min. Cool to 25℃ with the furnace to obtain the heat-treated product. Place the heat-treated product in a ball mill jar, add zirconia grinding balls at a mass ratio of 5:1, and ball mill at 300 r / min for 45 min. Sieve using a 75 μm sieve to obtain zirconium-cerium-boron-silicon controlled diffusion composite micro powder.

[0031] Preparation steps of titanium niobium phosphorus oxide carbon composite micro powder: Step B1: Add 20g tetrabutyl titanate to 40g anhydrous ethanol and stir for 20min at 25℃ and 300r / min to obtain a titanium source solution; add 18g ammonium niobate oxalate hydrate, 10g ammonium dihydrogen phosphate, 8g anhydrous glucose, 3g citric acid monohydrate and 1g polyethylene glycol 400 to 160g deionized water and stir for 30min at 25℃ and 400r / min. Adjust the pH to 2.5 with oxalic acid aqueous solution, and then add the titanium source solution dropwise at 25℃ and 400r / min for 30min. After the addition is completed, continue stirring for 60min to obtain a titanium-niobium-phosphorus-carbon composite slurry; grind and disperse the titanium-niobium-phosphorus-carbon composite slurry in a sand mill for 45min, controlling the slurry to have no obvious sedimentation and coarse particles, and then spray dry under the conditions of inlet air temperature of 150℃, outlet air temperature of 80℃ and feed rate of 15mL / min to obtain spherical precursor powder; Step B2: Place the spherical precursor powder in a tube furnace, purge with nitrogen for 30 min, and pretreat at 300℃ for 60 min at a nitrogen flow rate of 1 L / min to obtain pretreated powder. Continue to heat treat the pretreated powder in a nitrogen atmosphere at 760℃ for 60 min, cool it to 25℃ with the furnace, place it in a ball mill jar, add zirconia grinding balls at a grinding ball to material mass ratio of 5:1, ball mill at 300 r / min for 45 min, and sieve using a 75 μm sieve to obtain titanium niobium phosphorus oxide carbon composite micro powder.

[0032] Example 3 The difference between this embodiment and Embodiment 1 is that this embodiment provides a method for preparing a self-fluxing alloy material, including the following steps: Step S1: Add 76.81g of electrolytic nickel plate, 1.30g of metallic chromium granules, 0.25g of molybdenum powder, and 2.10g of electrolytic copper plate to a melting furnace, purge with argon gas for 30 minutes, and melt under an argon atmosphere to obtain a basic melt; add 12.00g of nickel-boron master alloy, 4.20g of metallic silicon, 6.43g of nickel-phosphorus master alloy, 0.25g of sponge titanium, 0.35g of metallic niobium powder, 0.040g of nickel-zirconium alloy, and 0.020g of nickel-beryllium alloy to the basic melt. The master alloy and 0.25g of nickel-cerium master alloy were refined under an argon atmosphere at a temperature of 1540℃ for 15min to obtain an alloy melt. The alloy melt was then atomized with argon gas at a pressure of 5.0MPa, and the atomized powder was collected. The powder was then sieved using a combination of 150μm and 45μm sieves to obtain powder with a particle size of 45-150μm, which was then used to obtain the main alloy powder. The main alloy powder was dried at 120℃ for 2h and then cooled to 25℃ to obtain dried main alloy powder. Step S2: Add 0.25g of zirconium-cerium-boron-silicon controlled diffusion composite micro powder and 0.20g of titanium-niobium-phosphorus oxide-carbon composite micro powder to the dry main alloy powder, mix in a three-dimensional mixer for 60min to obtain a mixed powder; degas the mixed powder under vacuum at 150℃ and a vacuum degree not exceeding 100Pa for 2h, cool to 25℃ and then sieve using a combination of 150μm and 45μm sieves to obtain powder with a particle size of 45-150μm to obtain the self-fluxing alloy material.

[0033] Preparation steps of zirconium-cerium-borosilicate controlled diffusion composite micropowder: Step A1: Add 240g of deionized water and 90g of ethanol to the reaction vessel, and stir for 10min at 25℃ and 300r / min to obtain a mixed solvent. Add 22g of zirconium nitrate pentahydrate, 14g of cerium nitrate hexahydrate, 25g of boric acid, 45g of acidic silica sol, 5g of citric acid monohydrate, and 3g of polyvinylpyrrolidone to the mixed solvent sequentially, and stir for 40min at 25℃ and 400r / min to ensure uniform dispersion of the components. Adjust the concentration with ammonia water. Adjust the pH to 4.5 and continue stirring at 25℃ and 400r / min for 60min to obtain a zirconium-cerium-borosilicate composite sol. Concentrate the zirconium-cerium-borosilicate composite sol at 70℃ until the material is in a uniform wet gel state with no obvious free-flowing liquid to obtain a wet gel. Spread the wet gel evenly in a ceramic dish with a thickness of 5mm and dry it at 120℃ for 12h to obtain a dry gel. Grind the dry gel and place it in a crucible, then calcine it at 540℃ for 2h to obtain the calcined product. Step A2: Place the calcined product in a tube furnace, purge with nitrogen for 30 min, and heat to 720℃ for 80 min at a nitrogen flow rate of 1 L / min. Cool to 25℃ with the furnace to obtain the heat-treated product. Place the heat-treated product in a ball mill jar, add zirconia grinding balls at a mass ratio of 5:1, and ball mill at 300 r / min for 45 min. Sieve using a 75 μm sieve to obtain zirconium-cerium-boron-silicon controlled diffusion composite micro powder.

[0034] Preparation steps of titanium niobium phosphorus oxide carbon composite micro powder: Step B1: Add 28g tetrabutyl titanate to 70g anhydrous ethanol and stir for 20min at 25℃ and 300r / min to obtain a titanium source solution; add 24g ammonium niobate oxalate hydrate, 16g ammonium dihydrogen phosphate, 12g anhydrous glucose, 5g citric acid monohydrate and 2g polyethylene glycol 400 to 220g deionized water and stir for 30min at 25℃ and 400r / min. Adjust the pH to 3.5 with oxalic acid aqueous solution, and then add the titanium source solution dropwise at 25℃ and 400r / min for 30min. After the addition is completed, continue stirring for 60min to obtain a titanium-niobium-phosphorus-carbon composite slurry; grind and disperse the titanium-niobium-phosphorus-carbon composite slurry in a sand mill for 45min, controlling the slurry to have no obvious sedimentation and coarse particles, and then spray dry under the conditions of inlet air temperature of 180℃, outlet air temperature of 95℃ and feed rate of 15mL / min to obtain spherical precursor powder; Step B2: Place the spherical precursor powder in a tube furnace, purge with nitrogen for 30 min, and pretreat at 360℃ for 90 min at a nitrogen flow rate of 1 L / min to obtain pretreated powder. Continue to heat treat the pretreated powder in a nitrogen atmosphere at 840℃ for 120 min, cool it to 25℃ with the furnace, place it in a ball mill jar, add zirconia grinding balls at a grinding ball to material mass ratio of 5:1, ball mill at 300 r / min for 45 min, and sieve using a 75 μm sieve to obtain titanium niobium phosphorus oxide carbon composite micro powder.

[0035] Comparative Example 1 The difference between this comparative example and Example 1 is that 0.175g of zirconium-cerium-boron-silicon controlled diffusion composite micropowder is not added in step S2, while the rest is the same as in Example 1.

[0036] Comparative Example 2 The difference between this comparative example and Example 1 is that 0.14g of titanium niobium phosphorus oxide carbon composite micro powder is not added in step S2, while the rest is the same as in Example 1.

[0037] Comparative Example 3 The difference between this comparative example and Example 1 is that 0.175g of zirconium-cerium-boron-silicon controlled diffusion composite micropowder and 0.14g of titanium-niobium-phosphorus oxide-carbon composite micropowder are not added in step S2, while the rest is the same as in Example 1.

[0038] A series of standardized tests were performed on the self-fluxing alloy materials described in Examples 1-3 and Comparative Examples 1-3, respectively.

[0039] Powders with a particle size of 45-150 μm were sieved from the self-fluxing alloy materials obtained in Examples 1-3 and Comparative Examples 1-3 as test samples.

[0040] During the initial melting temperature test, each test sample was made into a uniform pre-layer on the surface of a stainless steel substrate of the same material. The temperature was raised by induction heating and the surface temperature of the coating was recorded by a temperature recorder. The temperature at which the coating changed from a powder sintering state to a continuous melting and spreading state was observed. Each sample was tested at 3 independent locations, and the arithmetic mean of the 3 readings was taken as the initial melting temperature, in °C.

[0041] During the hardness test of the sprayed layer, the sprayed layer of each test sample was prepared using the same flame spraying process. After spraying, the cross-section of the sample was cut, inlaid, ground and polished. Vickers hardness test was performed in the middle of the sprayed layer, avoiding holes, inclusions and fusion lines. The test force was 98.07 N and the holding time was 10 s. Five effective indentation points were tested for each sample, and the average value was taken as the hardness of the sprayed layer. The result is expressed as HV10.

[0042] For V-notch impact energy absorption testing, a 15mm thick sprayed layer was prepared on the surface of steel with a width of 60mm and a length of 100mm using a multi-layer spraying method. Samples were taken from the sprayed layer using wire cutting and processed into 10mm×10mm×55mm V-notch impact specimens with a notch angle of 45°, a notch depth of 2mm, and a notch bottom radius of 0.25mm. Three specimens were tested for each sample, and the average value was taken as the V-notch impact energy, in J.

[0043] When testing the average grain size of the fusion line, the metallographic sample of the sprayed sample is cut along the direction perpendicular to the fusion line. After mounting, progressive polishing and etching, five fields of view near the fusion line are selected at 500×. The grain size is measured by the cut-off method and the average value is taken. The unit is μm.

[0044] During the boron diffusion-affected zone thickness test, the cross-sectional sample from the weld layer to the stainless steel substrate was polished and then an electron probe was used to perform boron element line scanning along the direction perpendicular to the fusion line. The area where the boron element signal is continuously higher than the substrate background value from the fusion line to the substrate side was taken as the boron diffusion-affected zone. Three lines were tested for each sample and the average value was taken, with the unit being μm.

[0045] During the fusion line crack count test, a 10mm long area was continuously observed and photographed along the fusion line at 200×. The number of visible cracks with a length of not less than 10μm was counted. Three areas were tested for each sample and the average value was taken. The results were expressed as cracks / 10mm.

[0046] The performance test data above are shown in Table 1.

[0047] Table 1: Performance Test Results As can be seen from the above, the initial melting temperature of Examples 1-3 is 947.8-958.4℃, which is in a similar low-temperature melting range to that of Comparative Examples 1-3 (953.4-957.9℃). This indicates that the addition of zirconium-cerium-boron-silicon controlled diffusion composite micro powder and titanium-niobium-phosphorus oxide-carbon composite micro powder did not destroy the low-melting self-melting system formed by the nickel-boron master alloy, metallic silicon, and nickel-phosphorus master alloy, and can still maintain melting characteristics suitable for low-temperature spray welding and remelting.

[0048] The hardness of the sprayed weld layer in Examples 1-3 is 431-451HV10, which is basically equivalent to 436-445HV10 in Comparative Examples 1-3. This shows that the present invention improves toughness and fusion line quality without significantly sacrificing the hardness and wear resistance of the sprayed weld layer.

[0049] In terms of impact performance, the V-notch impact absorption energy of Examples 1-3 was 78.9-86.5 J, which was higher than that of Comparative Example 1 (75.6 J), Comparative Example 2 (72.8 J), and Comparative Example 3 (67.4 J). Among them, Example 1 showed an improvement of about 28.3% compared with Comparative Example 3, which did not contain zirconium-cerium-boron-silicon controlled diffusion composite powder and titanium-niobium-phosphorus oxide-carbon composite powder. This indicates that the synergistic effect of zirconium-cerium-boron-silicon controlled diffusion composite powder and titanium-niobium-phosphorus oxide-carbon composite powder can improve the problems of high brittleness and insufficient impact toughness of the sprayed weld layer.

[0050] Regarding microstructure refinement, the average grain size of the fusion line in Examples 1-3 was 40.9-47.5 μm, which was significantly smaller than that of Comparative Example 1 (64.3 μm) and Comparative Example 3 (82.7 μm). This indicates that the zirconium-cerium-boron-silicon controlled diffusion composite micropowder can play a role in nucleation refinement and molten pool purification, thus solving the problems of coarse microstructure and obvious local segregation in the fusion line of existing self-fluxing alloys.

[0051] Regarding boron diffusion control, the thickness of the boron diffusion-affected zone in Examples 1-3 was 15.8-21.4 μm, significantly lower than that of Comparative Example 1 (28.5 μm), Comparative Example 2 (38.2 μm), and Comparative Example 3 (49.6 μm). Among them, Example 1 reduced the thickness by approximately 66.3% compared to Comparative Example 3. This indicates that the zirconium-cerium-boron-silicon diffusion-controlled composite micropowder and the titanium-niobium-phosphorus oxide-carbon composite micropowder can jointly mitigate the continuous diffusion of boron into the grain boundaries of the stainless steel matrix, solving the problem of fusion line grain boundary embrittlement and matrix-side microcrack tendency caused by excessive free boron.

[0052] Regarding fusion line cracks, no visible cracks were detected in Examples 1-3, while Comparative Examples 1, 2, and 3 showed 1 / 10mm, 2 / 10mm, and 4 / 10mm cracks, respectively. This indicates that the lack of zirconium-cerium-boron-silicon controlled diffusion composite powder alone resulted in insufficient microstructure refinement and purification, while the lack of titanium-niobium-phosphorus oxide-carbon composite powder alone resulted in insufficient interface toughening and boron migration inhibition. The most cracks were observed when both zirconium-cerium-boron-silicon controlled diffusion composite powder and titanium-niobium-phosphorus oxide-carbon composite powder were missing.

[0053] Therefore, compared with the comparative example, the present invention can improve impact toughness, refine fusion line structure, reduce the thickness of boron diffusion-affected zone and eliminate or reduce fusion line cracks while maintaining a low initial melting temperature and appropriate hardness. This solves the technical problems of high welding temperature, coarse grains in fusion lines, boron diffusion to the stainless steel side grain boundaries, embrittlement of the bonding interface and insufficient impact resistance of existing nickel-based self-fluxing alloys.

Claims

1. A self-fluxing alloy material, characterized in that, The components include the following parts by weight: 72.81-76.81 parts electrolytic nickel plate, 10.67-12.00 parts nickel-boron master alloy, 3.80-4.20 parts metallic silicon, 1.90-2.10 parts electrolytic copper plate, 1.10-1.30 parts metallic chromium particles, 0.15-0.25 parts molybdenum powder, 5.00-6.43 parts nickel-phosphorus master alloy, 0.15-0.25 parts sponge titanium, 0.25-0.35 parts metallic niobium powder, 0.015-0.040 parts nickel-zirconium alloy, 0.0075-0.020 parts nickel-beryllium master alloy, 0.15-0.25 parts nickel-cerium master alloy, 0.10-0.25 parts zirconium-cerium-boron-silicon controlled diffusion composite micro powder, 0.08-0.20 parts titanium-niobium-phosphorus oxide-carbon composite micro powder.

2. The self-fluxing alloy material according to claim 1, characterized in that, The preparation method of the zirconium-cerium-borosilicate controlled diffusion composite micropowder includes: A1. By weight, add 18-22 parts of zirconium nitrate pentahydrate, 10-14 parts of cerium nitrate hexahydrate, 18-25 parts of boric acid, 35-45 parts of acidic silica sol, 3-5 parts of citric acid monohydrate, and 1-3 parts of polyvinylpyrrolidone to a mixed solvent of 180-240 parts of deionized water and 60-90 parts of ethanol. Stir, adjust the pH to 4.0-4.5 with ammonia, and continue stirring to obtain a zirconium-cerium-borosilicate composite sol. Concentrate the zirconium-cerium-borosilicate composite sol to obtain a wet gel. Dry the wet gel to obtain a dry gel. Calcine the dry gel to obtain the calcined product. A2. The calcined product is placed in a nitrogen atmosphere for heat treatment, cooled, and the heat-treated product is obtained; the heat-treated product is ball-milled and sieved.

3. The self-fluxing alloy material according to claim 2, characterized in that, In step A1, the drying temperature is 100-120℃ and the drying time is 8-12h; the calcination temperature is 460-540℃ and the calcination time is 1-2h.

4. The self-fluxing alloy material according to claim 2, characterized in that, In step A2, the heat treatment temperature is 680-720℃ and the heat treatment time is 40-80 minutes.

5. The self-fluxing alloy material according to claim 1, characterized in that, The preparation method of the titanium niobium phosphorus oxide carbon composite micro powder includes: B1. By weight, add 20-28 parts of tetrabutyl titanate to 40-70 parts of anhydrous ethanol to obtain a titanium source solution; add 18-24 parts of ammonium niobate oxalate hydrate, 10-16 parts of ammonium dihydrogen phosphate, 8-12 parts of anhydrous glucose, 3-5 parts of citric acid monohydrate and 1-2 parts of polyethylene glycol 400 to 160-220 parts of deionized water, stir and disperse, adjust the pH to 2.5-3.5 with oxalic acid aqueous solution, and add the titanium source solution dropwise to obtain a titanium-niobium-phosphorus-carbon composite slurry; grind and disperse the titanium-niobium-phosphorus-carbon composite slurry, spray dry to obtain spherical precursor powder; B2. Pre-treat the spherical precursor powder in a nitrogen atmosphere to obtain pre-treated powder; then heat-treat the pre-treated powder in a nitrogen atmosphere, cool, ball-mill, and sieve.

6. The self-fluxing alloy material according to claim 5, characterized in that, In step B1, the inlet air temperature of the spray dryer is 150-180℃, and the outlet air temperature of the spray dryer is 80-95℃.

7. The self-fluxing alloy material according to claim 5, characterized in that, In step B2, the pretreatment temperature is 300-360℃ and the pretreatment time is 60-90 min; the heat treatment temperature is 760-840℃ and the heat treatment time is 60-120 min.

8. A method for preparing a self-fluxing alloy material according to any one of claims 1-7, characterized in that, step include: S1. Electrolytic nickel plates, metallic chromium granules, molybdenum powder, and electrolytic copper plates are added to a melting furnace and melted under an argon atmosphere to obtain a basic melt. Nickel-boron master alloy, metallic silicon, nickel-phosphorus master alloy, sponge titanium, metallic niobium powder, nickel-zirconium master alloy, nickel-beryllium master alloy, and nickel-cerium master alloy are added to the basic melt and refined under an argon atmosphere to obtain an alloy melt. The alloy melt is then atomized with argon gas and sieved to obtain a main alloy powder. The main alloy powder is dried to obtain a dried main alloy powder. S2. Add zirconium-cerium-boron-silicon controlled diffusion composite micro powder and titanium-niobium-phosphorus oxide-carbon composite micro powder to the dry main alloy powder, mix them to obtain a mixed powder; degas the mixed powder under vacuum and sieve it.

9. The method for preparing the self-fluxing alloy material according to claim 8, characterized in that, In step S1, the refining temperature is 1480-1540℃, the refining time is 8-15 min, and the argon atomization pressure is 3.0-5.0 MPa.

10. The method for preparing the self-fluxing alloy material according to claim 8, characterized in that, In step S2, the mixing time is 40-60 min, the vacuum degassing temperature is 120-150℃, and the vacuum degassing time is 1-2 h.